Pengaruh Budaya Kerja, Kompensasi dan Etos Kerja Terhadap Kinerja Karyawan Pada PT. Telkom Indonesia - Trisnawaty; Farhana Hasmin (STIM-LPI Makassar, 2023)
This study aims to examine the effect of work culture, compensation and work ethic on employee performance at PT. Telkom Makasar. The data in this study were obtained from each employee at PT. Telkom Makassar who is willing to be a respondent.This study used primary data by conducting direct research in the field by giving questionnaires/question sheets to 57 respondents. The data analysis method used is multiple linear regression analysis.The results showed that: partially, the variables of work culture, compensation and work ethic have a positive and significant effect on employee performance